Dielectric properties of myoglobin at 10 GHz by microwave cavity perturbation measurements. Issue 1 (2010) - Bonura, M.; Schirò, G.; Cupane, A.
Abstract : We report on the temperature dependence, at microwave (mw) frequency, of the imaginary part of the dielectric constant (ε″) in myoglobin powder samples with different hydration levels ( h ). The measurements have been performed by the cavity perturbation technique, in the range of temperature 80–345 K. The sample is located inside a glass capillary along the axis of a cylindrical copper cavity, resonating in the TE011 mode at 9.6 GHz, where the mw electric field has a node. By measuring the variation of the quality factor of the resonant cavity, one can extract the imaginary part of the dielectric constant. At temperatures higher than 230 K we observe an evident increase of the dielectric losses with increasing temperature; the effect scales almost linearly with hydration, indicating that it must be attributed to a relaxation of water in the hydration shell of the protein. Furthermore, at h ≥0.18, we observe a clear peak in the ε″ vs. T curve, that shifts towards lower temperatures upon increasing hydration; this shows that the activation enthalpy of the hydration water relaxation decreases with hydration. More in general, our data show that the technique of microwave cavity perturbation allows one to study the dynamics of water molecules in the hydration shell of proteins and to extend information obtained with dielectric techniques to the mw frequencies.